Cafenoel, from the processing of coffee to the benefit of Society: Requalification of São Manuel – SP cooperative complex - Tomazini, Lavínia Rodrigues; Strabeli, Giovana Innocenti (Technical and Scientific Journal Green Cities, 2022)
Based on urban necessity to provide social activities to the population, in addition to the need to give sense to the large underutilized areas, because they do not provide favor the appropriation of urban centers by society and minimize their potential, this work has as main objective to propose a requalification project of the complex of the cooperative of São Manuel – SP. To this end, the methodology was based on the theoretical foundation on industrial heritage, urban park and urban intervention. In addition, four related works were used to analyze their projects and a previous study where the technical visit was carried out. The project proposal and the needs program sought to respect the identity and history of the place, seeking attractiveness, functionality and taking full advantage of the spaces and their topography. KEYWORDS: Urbanistic project. Requalification. Social activities. Cooperative. Industrial heritage. Urban park.